Salvation in the Gospel of Mark: the death of Jesus and the path of discipleship - Markusse-Overduin, Gabrielle (Wipf and Stock Publishers, 2018)
The Gospel of Mark portrays Jesus making impossible demands on his disciples. They must follow him even if it costs them their lives. And, unsurprisingly, this proves to be impossible for them to do. They fail drastically in Mark's narrative and run from the scene as Jesus is arrested. Peter had been determined to stay by him unto death, but even he was not able to admit to knowing Jesus at that crucial moment. The strange thing is that Jesus made it clear that it is impossible to enter the Kingdom of God without this sort of radical discipleship. In this narrative study of salvation in the Gospel of Mark, this conundrum is studied closely with surprising results. An investigation of various socio-historical aspects of Mark's background elucidate the connection that Mark makes between the death of Jesus and the following of the disciples. And a study of Mark's narrative as a whole shows that Mark provides hope for those without courage to follow. If they continue to look and listen carefully, the mystery will be unveiled to them